The rhetoric of the Reformation - Matheson, Peter (T & T Clark academic paperbacks., 2004)
Peter Matheson has written the first study in English of the Reformation as a literary phenomenon. This book traces the first emergence of a 'public opinion' in European history. Using insights from social history, religion and literature, Professor Matheson explores the connection between the 'communal Reformation' and the outpouring of pamphlets in the early 1520's. These pamphlets helped to create a dynamic and subversive network of communication where language and structure were of equal importance. He also examines the relative strengths of polemical and dialogical approaches in winning adh.